Europe Faces Europe Narratives from Its Eastern Half - Fornäs, Johan (Intellect, 2017)
Europe Faces Europe examines Eastern European perspectives on European identity. The contributors to this volume map narratives of Europe rooted in Eastern Europe, examining their relationship to philosophy, journalism, social movements, literary texts, visual art, and popular music. Moving the debate and research on European identity beyond the geographical power center, the essays explore how Europeanness is conceived of in the dynamic region of Eastern Europe. Offering a fresh take on European identity, Europe Faces Europe comes at an important time, when Eastern Europe and European identity are in an important and vibrant phase of transition.